Publisher’s Note: Continued Publication of International Journal of Plant Biology by MDPI - Enric Sayas (International Journal of Plant Biology, 2022)
The International Journal of Plant Biology (ISSN: 2037-0164) was launched in 2010 and publishes international and multidisciplinary research in the different subdisciplines of plant biology [...]